Anxiety of Tengo Kawana in Town Of Cats Short Story by Haruki Murakami 2011 - Ahmad Saifudin; Widyashanti Anindita (English Language and Education Spectrum, 2023)
The aims of this research are to find out the structural personalities (id, ego, and superego) of Tengo Kawana from psychoanalysis in the Town of Cats short story by Haruki Murakami 2011 and to find out the kinds of anxieties of Tengo Kawana viewed from psychoanalysis appears in the Town of Cats short story by Haruki Murakami 2011. To find the personalities and the anxiety of the major Character on the novel, the researcher used Sigmund Freud Theory. This research is descriptive qualitative by analyzing the novel into description and explanation. The data are collected by taking a note technique. The writer used referential method for analyzing the data by looking for Tengo Kawana’s utterances and narration, making note from the problem, classifying the data based on the structure of personality and anxiety. Analyzing the data is based on structure of personality and anxiety of Tengo Kawana in Town of Cats short story by Haruki Murakami 2011, drawing conclusion. The conclusion of this research shows that there are id, ego, superego and the kinds of anxiety appearing within Town of Cats short story by Haruki Murakami 2011.